HUBUNGAN PERSEPSI SISWA TENTANG KEMAMPUAN MENGAJAR MAHASISWA PRAKTEK LAPANGAN KEPENDIDIKAN TERHADAP MOTIVASI BELAJAR MATA PELAJARAN PRODUKTIF - Yogi Irdes Putra; Ahmad Ridoh (Jurnal Muara Pendidikan, 2022)
This study aims to determine the description of students 'perceptions about the ability to teach students educational practice and student motivation, as well as to determine whether students' perceptions about the ability to teach students the educational practice toward learning motivation of productive training class XI at SMKN 9 Padang the third semester in academic year 2020/2021 has a positive and significant relationship. This research is quantitative with associative research type. Instrument used to collect data was a questionnaire. To measure students' perceptions about the ability to teach students PLK and learning motivation to use a questionnaire compiled by the Likert Scale models. Based on the research that has been conducted on the research population are Catering students’ class XI at SMKN 9 Padang Academic Year 2020/2021 with a population of 119 people and sample of 93 people. The result in this research that positive and significant relationship between students' perceptions about the teaching students’ PKL ability toward learning motivation of productive training subject class XI at SMKN 9 Padang the third semester Academic Year 2020/2021, This is indicated by the overall students perception on the teaching students PLK ability in the Very Good category (85.07%), while the overall learning motivation in the Very Good category (83.31%). Students’ perceptions about the ability to teach students PLK affect students’ motivation by 4.5% and the rest of other factors. Keywords: teaching, ability, motivation